REFLEKSI AWAL TERBENTUKNYA DINASTI ABBASIYAH - Sintia Aprianty (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This article intends to provide an overview of (The chronology of the formation of the Abbasid dynasty, especially in the early days of its establishment in Baghdad). In collecting data, this research uses data analysis methods through virtual sources. In carrying out this analysis, the researcher used data reduction, data display and drawing conclusions. The author concludes that the Abbasid Daula period is also called